1994
DOI: 10.2172/10105788
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate scale borehole (Room C): In situ data report (January 1989--June 1993)

Abstract: Approved for public releaa&hIatribution la unlimited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…A series of cylindrical-excavation creep closure tests have been conducted to investigate the effect of scale on salt creep (Fuenkajorn and Daemen, 1988;Doeven et al, 1983;Munson et al, 1994Munson et al, , 1995b, motivated by model predictions that did not match observed room closure in early WIPP excavations (Tyler et al, 1988;). The differences were eventually not attributed to scale, but to creep model parameters estimated from lab test data.…”
Section: Representative Scales In Saltmentioning
confidence: 99%
“…A series of cylindrical-excavation creep closure tests have been conducted to investigate the effect of scale on salt creep (Fuenkajorn and Daemen, 1988;Doeven et al, 1983;Munson et al, 1994Munson et al, , 1995b, motivated by model predictions that did not match observed room closure in early WIPP excavations (Tyler et al, 1988;). The differences were eventually not attributed to scale, but to creep model parameters estimated from lab test data.…”
Section: Representative Scales In Saltmentioning
confidence: 99%
“…Heating continued in Room B until January 1989 (although the B042 heater failed in February 1987 ), and in Room A1 until July 1990 (Munson et al, 1992). Borehole wall temperatures in the two Room A1 heaters had reached an approximate steady-state temperature of 50°C after 100 days of heating.…”
Section: Wipp In Situ Moisture Release Experimentsmentioning
confidence: 99%
“…The size of the excavation of the test is about a factor of 10 smaller than the rooms. Even though further analysis of the basic technology suggested that the discrepancy was the result of an inadequacy of the constitutive model and the details of the simulation, which was subsequently shown to be the case [12,13], Geomechanical Evaluation (Room G) [14], and the multipass mining sequence closure data for all the test rooms and shafts, including the intermediate scale test [15].…”
mentioning
confidence: 99%